1994
DOI: 10.3801/iafss.fss.4-551
|View full text |Cite
|
Sign up to set email alerts
|

Plume Behavior In A Confined Tall And Narrow Space-as One Of Sub-models Of Plume For An Atrium Fire-

Abstract: Experimental study on a flow behavior of flame and plume was carried out using a full scale atrium model and a reduced one having low-inlet and high-outlet openings under natural ventilation condition. Similarities between these spaces were pursued on representative ATIT in the space and on the inflow behavior which is represented by Froude number estimated at the lower opening(s). Interaction between inflow and flame/plume in the confined space was investigated using the reduced model with some variations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Hiroomi et al [2] have demonstrated systematic changes in observed plume structure as a result of confinement in tall, narrow enclosures. Bilger [3] has advocated the use of field models, in particular those based on k -E models of turbulence, to study issues of this type.…”
Section: Introductionmentioning
confidence: 99%
“…Hiroomi et al [2] have demonstrated systematic changes in observed plume structure as a result of confinement in tall, narrow enclosures. Bilger [3] has advocated the use of field models, in particular those based on k -E models of turbulence, to study issues of this type.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that the hazards because of the stack effect are greater than those from turbulent mixing. To understand the transport characteristics of thermal smoke driven by the stack effect in shafts, many studies have been carried out through both experiments (Hiroomi et al, 1994;Benedict, 1999;Su et al, 2011;Shi et al, 2014) and simulations (Xiao et al, 2008;Sun et al, 2011;Harish and Venkatasubbaiah, 2013;Chen et al, 2016). However, the sidewalls of the vertical shaft have commonly been assumed to be sealed in previous studies, with only a single opening near the Fire-induced smoke flow ceiling.…”
Section: Introductionmentioning
confidence: 99%